Triglyceride-Rich Lipoprotein Modulates Endothelial Vascular Cell Adhesion Molecule (VCAM)-1 Expression via Differential Regulation of Endoplasmic Reticulum Stress - Wang, Ying I.; Bettaieb, Ahmed; Sun, Chongxiu; DeVerse, J. Sherrod; Radecke, Christopher E.; Mathew, Steven; Edwards, Christina M.; Haj, Fawaz G.; Passerini, Anthony G.; Simon, Scott I. (PloS one, 2013)
Circulating triglyceride-rich lipoproteins (TGRL) from hypertriglyceridemic subjects exacerbate endothelial inflammation and promote monocyte infiltration into the arterial wall. We have recently reported that TGRL isolated from human blood after a high-fat meal can elicit a pro- or anti-atherogenic state in human aortic endothelial cells (HAEC), defined as up- or down-regulation of VCAM-1 expression in response to tumor necrosis factor alpha (TNFα) stimulation, respectively. A direct correlation was found between subjects categorized at higher risk for cardiovascular disease based upon serum triglycerides and postprandial production of TGRL particles that increased VCAM-1-dependent monocyte adhesion to inflamed endothelium. To establish how TGRL metabolism is linked to VCAM-1 regulation, we examined endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) pathways. Regardless of its atherogenicity, the rate and extent of TGRL internalization and lipid droplet formation by HAEC were uniform. However, pro-atherogenic TGRL exacerbated ER membrane expansion and stress following TNFα stimulation, whereas anti-atherogenic TGRL ameliorated such effects. Inhibition of ER stress with a chemical chaperone 4-phenylbutyric acid decreased TNFα-induced VCAM-1 expression and abrogated TGRL's atherogenic effect. Activation of ER stress sensors PKR-like ER-regulated kinase (PERK) and inositol requiring protein 1α (IRE1α), and downstream effectors including eukaryotic initiation factor-2α (eIF2α), spliced X-box-binding protein 1 (sXBP1) and C/EBP homologous protein (CHOP), directly correlated with the atherogenic activity of an individual's TGRL. Modulation of ER stress sensors also correlated with changes in expression of interferon regulatory factor 1 (IRF-1), a transcription factor of Vcam-1 responsible for regulation of its expression. Moreover, knockdown studies using siRNA defined a causal relationship between the PERK/eIF2α/CHOP pathway and IRF-1-mediated VCAM-1 expression. We conclude that ER stress and the UPR contribute to the regulation of Vcam-1 transcription as a function of the atherogenic nature of TGRL.